Effect of Integrated Weed Management Practices on Weed Growth and Productivity of Pigeonpea (Cajanus cajan) - Singh, Guriqbal; Virk, H. K. (International Journal of Bio-resource and Stress Management, 2018)
Field experiments were conducted for three years (2009–2011) on a loamy sand soil to study the effect of integrated weed management practices on weed growth and productivity of pigeonpea. Two hand weedings [25 and 50 days after sowing (DAS)] and pendimethalin (0.45 or 0.75 kg ha-1) in integrated with hand weeding (50 DAS) or directed spray of paraquat [0.48 kg ha-1 at 6 or 8 weeks after sowing (WAS)] on weeds between the crop rows using a hood resulted in higher weed control efficiency and grain yield. Uncontrolled weeds caused 14.6–123.8% reduction in pigeonpea grain yield in different years. All the treatments of herbicides viz. pendimethalin (0.45 or 0.75 kg ha-1) as pre-emergence, paraquat (0.48 kg ha-1) and imazethapyr (75 g ha-1) as post-emergence, applied either alone or in integration significantly reduced dry weight of weeds at 80 DAS and at harvest compared to weedy check. Application of pendimethalin @ 0.75 kg ha-1 followed by hand weeding (50 DAS) and two hand weedings (25+50 DAS) recorded the highest weed control efficiency. In the treatment where crop sown in rows 67.5 cm apart, interculture using a tractor provided effective weed control and high grain yield. Application of pendimethalin (0.45 or 0.75 kg ha-1) as pre-emergence and tank mix application of imazethapyr (75 g ha-1) +quizalofop ethyl (50 g ha-1) as post-emergence either alone or in integration with hand weeding at 50 DAS also reduced the dry weight of weeds and increased the grain yield.